Limited English-Proficient Students: Analysis of Subjective Experiences - Diana Karanauskienė; Asta lil; Lina Danilevičienė (Lithuanian Sports University, 2018)
Background. Many long-term adolescent and adult learners experience persistent academic underachievement in English in spite of many years of schooling. Students pertaining A2 level can be classified as Limited English- Proficient Learners who have not acquired English proficiency as required by the university, state and European guidelines. Research aim was to analyse the perceptions of underachieving students of reasons of their failure to gain English language proficiency of the required level aiming at increasing the knowledge on the problem and providing possible solutions for improvement. Methods.  Participants'  perceptions  of  their  underachievement  reasons  were  elicited  through  individual unstructured in-depth interviews. Data analysis occurred concurrently with data collection using grounded theory as a method for analysing the data. Member checks with several research participants, reflexive journaling and peer debriefing were also utilized to ensure trustworthiness of the study . Results.  The  examination  of  interview  transcripts  revealed  two  big  themes  concerning  the  students' underachievement in the English language: internal and external causes for being limited English-proficient learner. External causes were conditions for learning English at school and at the university: poor learning in primary grades, underestimated value of knowing and learning English at school, inadequate conditions for informal learning, and poor organization of English lessons. University factors mentioned were too few contact hours for English classes, inconvenient time-table, and lack of time due to other activities. Internal factors were fear to look unacceptable (resulting in the inactivity in the classes), lack of self-confidence, too much self-criticism, laziness, procrastination, finding faults with others, inadequate perception of the course, poor attitudes towards the course, lack of internal motivation, rating the module of English as a second-rate course, not knowing how to learn the language, and, what is most important, absence of self-study skills. Conclusions. Internal factors conditioning underachievement in the English language proved to be much more important than the external ones. Poor self-esteem, lack of motivation and poor attitudes towards the course suggest the need of the individualization of teaching/learning and psychological counselling. Lack of self-study skills can predict poor academic achievements in other university courses, which could result in drop-outs. This suggests the need of coaching students in learning skills. The collected data show that the teacher also plays a crucial role in language learning, however, the wider societal, cultural and psychological context should be articulated in further possible research as well. Study programmes at tertiary level should be designed to encourage both internal and external  motivation  of  students  to  study  foreign  languages  as  an  indispensable  factor  for  developing  a  full-rate personality. Keywords:  limited English - proficient learners, qualitative research, underachievement.